Ethnobotany of the Teo Sweet Potato Plant (Tacca leontopetaloides) as an Alternative Food for the Bajo Tribe - Lambera, Walisa Ardita; Solang, Margaretha; Ahmad, Jusna; Lamanganjo, Chairunnisah J; Isra, Muhammad (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2026)
Teo yam (Tacca leontopetaloides) is a coastal local plant with potential as an alternative food source; however, its utilization is declining due to decreasing local knowledge among communities. This study aimed to examine the level of knowledge of the Bajo community regarding teo yam, traditional processing techniques, and its utilization as an alternative food source. The study was conducted from January to April 2026 in Bumi Bahari, Torosiaje Jaya, and Torosiaje Villages, Popayato Subdistrict, Pohuwato Regency, using a qualitative descriptive method with an ethnobotanical approach. Data were collected through observation, semi-structured interviews, and documentation involving 60 informants selected through snowball sampling. The results showed that community knowledge varied by age group, with adults and the elderly demonstrating higher levels of knowledge than younger generations, indicating a decline in local knowledge transfer. Teo tubers are traditionally processed into flour through peeling, grating, soaking, settling, drying, and straining, before being used to prepare traditional foods such as cendol, loho bua, onde-onde, cucur, and ledo. The findings suggest that teo yam has potential as an alternative carbohydrate source while highlighting the importance of preserving local knowledge to sustain its utilization.